2011
DOI: 10.1371/journal.pone.0026825
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions and Rheological Properties of Exopolysaccharide Produced by Deep-Sea Bacterium Zunongwangia profunda SM-A87

Abstract: Zunongwangia profunda SM-A87 isolated from deep-sea sediment can secrete large quantity of exopolysaccharide (EPS). Response surface methodology was applied to optimize the culture conditions for EPS production. Single-factor experiment showed that lactose was the best carbon source. Based on the Plackett–Burman design, lactose, peptone and temperature were selected as significant variables, which were further optimized by the steepest ascent (descent) method and central composite design. The optimal culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Several authors have shown that several bacterial strains could produce EPS when grown in whey or whey derivatives. Sun et al (2014) reported that the strain Zunongwangia profunda SM-A87 could grow in whey and produce the highest amount of EPS (17.2 g/L) reported for a marine bacterium; this polymer displays antioxidant activity and is of industrial interest since it has optimum biosorption capacities for Cu(II) and Cd(II) and has good rheological properties to enhance oil recovery (Liu et al 2011). Also, the strain Rhizobium radiobacter S10, isolated from kefir grains, is able to produce 2.8 g/L of a 3.03−10 6 Da polymer with interesting thickener or stabilizer properties during its growth in whey ).…”
Section: Exopolysaccharidesmentioning
confidence: 99%
“…Several authors have shown that several bacterial strains could produce EPS when grown in whey or whey derivatives. Sun et al (2014) reported that the strain Zunongwangia profunda SM-A87 could grow in whey and produce the highest amount of EPS (17.2 g/L) reported for a marine bacterium; this polymer displays antioxidant activity and is of industrial interest since it has optimum biosorption capacities for Cu(II) and Cd(II) and has good rheological properties to enhance oil recovery (Liu et al 2011). Also, the strain Rhizobium radiobacter S10, isolated from kefir grains, is able to produce 2.8 g/L of a 3.03−10 6 Da polymer with interesting thickener or stabilizer properties during its growth in whey ).…”
Section: Exopolysaccharidesmentioning
confidence: 99%
“…According to previous studies dealing with the influence of pH on the viscosity of 209 polysaccharide solutions, the increase of viscosity at pH 4.0 and 6.0 may be due to an increase 210 of the ionization degree of carboxyl groups in EPS22 polysaccharide (Maalej,Boisset,et al,211 2014) leading to the extension of the polymer molecules (Liu et al, 2011). However, the 212 decrease of the EPS22 viscosity at very acidic (pH 1.0) or alkaline conditions (pH 10.0) may 213 be attributed to the screening effect of excess alkali on the negatively charged polysaccharide 214 molecules (Liu et al, 2011).…”
mentioning
confidence: 97%
“…However, the 212 decrease of the EPS22 viscosity at very acidic (pH 1.0) or alkaline conditions (pH 10.0) may 213 be attributed to the screening effect of excess alkali on the negatively charged polysaccharide 214 molecules (Liu et al, 2011). Another explanation was reported by Li and Hou (2011) who 215 suggested that the good pH stability of the SM-A87 EPS solution may be attributed to the 216 hyper-branched structure of the polymer's molecules.…”
mentioning
confidence: 99%
“…The strain was cultured as previously described (11). Briefly, the strain was first cultured on a marine agar medium (10 g/liter peptone, 5 g/liter yeast extract, 15 g/liter agar, and artificial seawater) at 30°C for 1 day.…”
mentioning
confidence: 99%